Wave power atlas of Eastern Mediterranean and Aegean Seas - Ayat, Berna (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Wave energy potential of the Eastern Mediterranean Sea Basin was assessed and characterized. Wave fields obtained from 3rd generation spectral wave model for years 1994-2009 by using wind data from European Center for Medium-Range Weather Forecasts (ECMWF) were used in order to calculate the wave powers. Wave model was calibrated using the wave measurements conducted at three different stations. Wave model simulated the wave characteristics such as significant wave heights (H-s) and mean wave periods (T-m) with high accuracy. Wave power atlas was generated based on 15-year time-averaged wave data. Also wave power roses and distribution tables in means of periods and heights for different regions were presented. Mean wave power found to be below 2 kW/m along the coasts of the whole model area. The most energetic coast of the Southern Mediterranean Basin is Egyptian coast lying between Nile Delta and the Libya border with a potential of above 4 kW/m. Some regions along the coasts of some Greek Islands also have potential above 4 kW/m within the Aegean Sea Basin. The eastern part of the model area is found to be the least energetic. The most energetic sea states have significant wave heights between 1 and 4 m and wave energy periods between 4 and 8 s. Seasonal trends were also investigated in this study. The mean wave power in winter is roughly 2 times larger than annual mean. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Wave energy; Eastern Mediterranean Sea; Aegean Sea; Spectral wave modeling; ENERGY RESOURCE; Thermodynamics; Energy & Fuels